Karakteristik Organoleptik Jelly Drink Kulit Manggis (Garcinia mangostana L.) dan Kajian Konsentrasi Rumput Laut (Eucheuma spinosum) sebagai Pangan Fungsional - Lukman Hudi; Rahmah Utami Budiandari; Syaiful Anam (Program Studi Pendidikan Teknologi Agroindustri, UPI (Universitas Pendidikan Indonesia), 2023)
Jelly drink is one of the hunger delay drinks, made from fruit juice mixed with sugar and hydrocollid to form a gel structure, it has a solid texture, the gel is easily crushed but the gel is still felt in the mouth. Eucheuma spinosum seaweed is one of the best types of seaweed in Indonesia, generally used as a thickening agent. Mangosteen (Garcinia mangostana L.) is one of Indonesia's special fruits. Mangosteen skin contains xanthones which are antioxidants. The xanthone content is 107.76 mg/100 g, and easily damaged, to increase shelf life one of which is processed into jelly drink. Mangosteen skin extract is formulated with Eucheuma spinosum pulp to make jelly drink. This study aims to determine the organoleptic characteristics and consumer acceptance of jelly drink mangosteen rind and seaweed pulp. The method was design a factorial randomized block design. The first factor is proportion of mangosteen skin extract and second factor was contentration of pure seaweed with the first factor being the proportion of mangosteen skin extract and the second factor being the concentration of seaweed pulp. The best treatment results showed the average results of the organoleptic taste score 4.40, aroma organoleptic 4, color organoleptic 4.47 and organoleptic texture 4.47.